Aqueous Cr (VI) removal performance of an invasive plant-derived biochar modified by Mg/Al-layered double hydroxides - Li, Xiaoying; Shi, Zhaoji; Zhang, Jiaen; Gan, Tian; Xiao, Zeheng (Colloid and interface science communications, 2023)
In this study, MgAl layered double hydroxides (Mg-Al/LDH)-decorated invasive plant (Praxelis clematidea)-derived biochar (MgAl/LDH-PBC) were prepared by the co-precipitation method. The characterization results revealed that the modified biochar surface offered more active adsorption sites, facilitating the Cr (VI) adsorption. MgAl/LDH-PBC showed an excellent adsorption capacity of 177.88 mg/g in a monolayer, with a rapid uptake equilibrium within 180 min. In addition, even after five cycles, the desorption rates remained at about 85%, and the Cr (VI) adsorption was quite stable despite the presence of a number of other ions. Moreover, MgAl/LDH-PBC bonded efficiently with Cr (VI) via electrostatic interaction, oxidation-reduction reaction, ion-exchange reaction, complexation, and co-precipitation. Based on these findings, MgAl/LDH-PBC may be used as an adsorbent for the removal of Cr (VI) from sewage and the management of invasive plant species. [Display omitted] •Mg/Al-LDH was embedded in invasive plant-derived biochar (MgAl/LDH-PBC).•MgAl/LDH-PBC is a porous material with a high specific surface area.•The maximum uptake of Cr (VI) by MgAl/LDH-PBC was 177.88 mg/g.•The adsorption mechanism involved physical and chemical interactions.